Surgical Management of Ischemic Priapism: what are the New Options? - Rohit Badia; Sidney Roberts; Alexandria Hertz; Allen Morey; Maia VanDyke (International Brazilian Journal of Urology)
ABSTRACT Ischemic priapism is a true urologic emergency. Prompt intervention is required to alleviate the compartment syndrome and restore perfusion to the corporal bodies; failure to do so results in irreversible damage, fibrosis, and profound erectile dysfunction. This paper's objective is to review current literature surrounding the management options for ischemic priapism, focusing on newer surgical techniques. A PubMed database search was performed in June 2024, encompassing the terms "priapism," and "surgical management." Articles were reviewed by two authors independently and included if they were deemed to pertain specifically to management of ischemic priapism. In the acute setting (certainly for priapism lasting <24 hours), management is often successful using bedside maneuvers such as aspiration, irrigation, and injection of sympathomimetic agents. For more prolonged priapism, more aggressive intervention is often warranted. Newer tunneling techniques—including penoscrotal decompression and the corporal snake maneuver—have shown promising preliminary results, not just in terms of priapism resolution but also perhaps sexual function recovery.